2004
DOI: 10.5694/j.1326-5377.2004.tb05799.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in adolescents and young adults: treatment and outcome in Victoria

Abstract: Objectives: To describe the location of treatment, recruitment to clinical trials and outcomes for adolescents and young adults treated for cancer in Victoria. Design and setting: Retrospective review of all adolescents and young adults aged 10–24 years diagnosed with cancer between 1992 and 1996, identified from the Victorian Cancer Registry. Main outcome measures: Treatment regimen (clinical trial, treatment protocol or neither), compliance with treatment and 5‐year survival. Results: Questionnaires were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…19 Another study found that only 14% of adolescents aged 16 to 19 years were treated at a pediatric institution. 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Another study found that only 14% of adolescents aged 16 to 19 years were treated at a pediatric institution. 20 …”
Section: Resultsmentioning
confidence: 99%
“…Of 91 cases with new cancer diagnoses treated at the pediatric center, 24 (26%) were enrolled, whereas only 5 of 121 (4%) cases with new cancer diagnoses treated at the adult center were enrolled in a clinical trial 24 A study in Australia showed that adolescents aged 10 to 19 years were more likely to be enrolled in a clinical trial if treated at a pediatric institution rather than at an adult institution (38% vs 3%). 20 Even if adolescents are seen at a pediatric institution, appropriate clinical trials may not be available. In a study in 640 patients with newly diagnosed cancer at a pediatric institution, 38% of patients under the age of 15 years were enrolled in a clinical trial and 27% of patients aged 15 to 22 years were enrolled in a clinical trial 25 More than half of the older patients were not enrolled because a trial was not available.…”
Section: Resultsmentioning
confidence: 99%
“…Although the peak incidence of ESFT is during the AYA years, these patients have a worse survival compared to a pediatric population [27]. The reasons behind this comprise a combination of biological differences [27,28], delayed diagnosis, poorer treatment compliance [29,30], psychosocial overlay and limited involvement in clinical trials [31,32]. With regards to biological differences, in the EURO-Ewing 99 protocol [10], increasing age and male gender was associated with less toxicity using VIDE chemotherapy, a protocol similar to VDC/IE.…”
Section: Discussionmentioning
confidence: 99%
“…It was established from the clinical services at the Royal Children's Hospital (RCH) and the Monash Medical Centre (MMC), between which over 95% of children under 10 years of age and 83% of children aged 10–15 years with cancer within the State of Victoria, Australia, are treated [8]. Children were eligible for inclusion if they had a diagnosis of any cancer before age 15 and when initial treatment was given at one of the participating centres between October 1998 and October 2002.…”
Section: Methodsmentioning
confidence: 99%